1992
DOI: 10.1021/jm00091a003
|View full text |Cite
|
Sign up to set email alerts
|

2-Alkynyl derivatives of adenosine and adenosine-5'-N-ethyluronamide as selective agonists at A2 adenosine receptors

Abstract: In the search for more selective A2-receptor agonists and on the basis that appropriate substitution at C2 is known to impart selectivity for A2 receptors, 2-alkynyladenosines 2a-d were resynthesized and evaluated in radioligand binding, adenylate cyclase, and platelet aggregation studies. Binding of [3H]NECA to A2 receptors of rat striatal membranes was inhibited by compounds 2a-d with Ki values ranging from 2.8 to 16.4 nM. 2-Alkynyladenosines also exhibited high-affinity binding at solubilized A2 receptors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 1 publication
4
105
0
Order By: Relevance
“…5-Amino-9-chloro-2-(2 -furyl) -1,2,4 -triazolo[1,5 -c]quinazoline (CGS 15943) was kindly supplied by Ciba-Geigy (Summit, NJ, U.S.A.). 2-Hexynyl-5'-N-ethylcarboxamidoadenosine (2HE-NECA) was synthesized by Dr G. Cristalli (Department of Chemical Sciences, University of Camerino, Camerino, Italy) (Cristalli et al, 1992)…”
Section: Discussionmentioning
confidence: 99%
“…5-Amino-9-chloro-2-(2 -furyl) -1,2,4 -triazolo[1,5 -c]quinazoline (CGS 15943) was kindly supplied by Ciba-Geigy (Summit, NJ, U.S.A.). 2-Hexynyl-5'-N-ethylcarboxamidoadenosine (2HE-NECA) was synthesized by Dr G. Cristalli (Department of Chemical Sciences, University of Camerino, Camerino, Italy) (Cristalli et al, 1992)…”
Section: Discussionmentioning
confidence: 99%
“…The iodoNECA (14) 14-16 with the appropriate mercaptans in dry DMF at 120 °C using potassium carbonate as a catalyst (Scheme 1 and Table 1). The receptor-stimulated adenylyl cyclase activity expressed as EC 50 , nM.…”
mentioning
confidence: 99%
“…Compound 5 was prepared by a modification of the procedure reported by Cristalli et al 6 Compound 8 was prepared by a modification of the procedure reported by Rieger et al…”
Section: Methodsmentioning
confidence: 99%